CHANGES OF VARIABILITY HEART RATE INDEXES DURING NEUROFEEDBACK IN DIFFERENT QUALIFICATION SPORTSMEN - L. P. Cherapkina (Бюллетень сибирской медицины)
The increasing of total heart rate spectral power and parasympathetic activity (by indexes of the variation pulsomeasuring) during neurofeedback sessions intended for electroencephalogram (EEG) power in alpha-band increasing in masters of sport, master of sport of international level (n = 26), candidates to master of sport (n = 25) and sportsmen of lower qualification (n = 23) were accompanied by different changes of structure of heart rate spectral.